2012
DOI: 10.1002/adfm.201101985
|View full text |Cite
|
Sign up to set email alerts
|

Prestrain‐Free Dielectric Elastomers Based on Acrylic Thermoplastic Elastomer Gels: A Morphological and (Electro)Mechanical Property Study

Abstract: Recent efforts have established that thermoplastic elastomer gels (TPEGs) composed of styrenic triblock copolymers swollen with a midblock-selective solvent exhibit remarkable electromechanical properties as high-performance dielectric elastomers. This class of electroactive polymers typically requires high electric fi elds for actuation, and a shortcoming that continues to thwart the widespread commercialization of such materials in general is the need to apply mechanical prestrain prior to electroactuation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
48
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 59 publications
2
48
0
Order By: Relevance
“…Physical incorporation of a midblock-selective, low-volatility organic solvent into a nonpolar TPE tends to swell the molecular network, thereby yielding a thermoplastic elastomer gel (TPEG) at low copolymer concentrations (but above the critical gel concentration). [20][21][22][23] These soft materials possess highly tunable (electro)mechanical properties and are of considerable interest in the development of dielectric elastomers, [24][25][26][27] fl exible electronics [ 28 ] and microfl uidic substrates. [ 29 ] In some instances, ABA-triblock copolymers have been specifi cally designed with a nonionic hydrophilic (typically ethoxylated [30][31][32] ) middle block to facilitate inclusion of water, ionic liquids, or other polar liquids for use in contemporary technologies such as personal-care products, fuel cells, and separation membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Physical incorporation of a midblock-selective, low-volatility organic solvent into a nonpolar TPE tends to swell the molecular network, thereby yielding a thermoplastic elastomer gel (TPEG) at low copolymer concentrations (but above the critical gel concentration). [20][21][22][23] These soft materials possess highly tunable (electro)mechanical properties and are of considerable interest in the development of dielectric elastomers, [24][25][26][27] fl exible electronics [ 28 ] and microfl uidic substrates. [ 29 ] In some instances, ABA-triblock copolymers have been specifi cally designed with a nonionic hydrophilic (typically ethoxylated [30][31][32] ) middle block to facilitate inclusion of water, ionic liquids, or other polar liquids for use in contemporary technologies such as personal-care products, fuel cells, and separation membranes.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, the triblock elastomers are easily processed. Some commercially available ABA triblock copolymer elastomers have been explored as dielectric elastomers . It was found that the single component of the triblock copolymer showed poor electromechanical performance .…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we discovered that a commercially available elastomer, VHB 4910, demonstrates a good compromise of the mechanical strength and the self‐healing ability. Due to its good mechanical strength and electro‐active properties, this material shows a potential to be used as a dielectric actuator . In addition, it's application in artificial muscles has been suggested .…”
Section: Introductionmentioning
confidence: 99%